Determinant factors on farmers household food security in greater Malang - Pudjihardjo, M. (Opción, 2020)
This study aims to analyze the determinants as to what affects the household food security of farmers. The study was comparative by comparing the results of model calculations in 3 regions in Greater Malang, including Batu City, Malang City, and Malang Regency. The results showed that the chance of a food-insecure (Y0) household is high for households that do not have a mode of transportation. In conclusion, the similarity of points is evidenced by the form of output, which has the same significance level and coefficient in each of these regions.